Role of Tertiary Education in Addressing Problem of Language Extinction in Nigeria (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This paper discussed the roles of tertiary institutions in addressing the problem of native language extinction in Nigeria. The paper used secondary data that were collected from print and online publications. Adopting content analysis and elimination methods that were used for data selection. The paper identified some of the roles of tertiary institutions to includes; teaching of the importance of local language preservation, establishment of more department for local languages, establishment of centre for studies of local language, research on language preservation, provision community service that are based public sensitization programme on local language preservation and provision of technical assistance to government on policy formulation. Based on this, the paper hereby recommended that the government should partner with tertiary institutions across the country on preservation of local languages in Nigeria. Government should direct all tertiary institutions in the country to come with programmes on local languages preservation. Government should provide both human and materials resources to all tertiary institutions to run and implement all programme designed for local language preservation from extinction in Nigeria.